Retrospective Evaluation of Rabbit Antithymocyte Globulin Induction in Heart Transplant Patients. Issue 6 (26th May 2022) - Lee, Grace Pui-Yun; Cheng, Richard K.; Vasbinder, Alexi; Wu, Sixuan; Wong, Beatrice; Farris, Stephen D.; Fishbein, Daniel; Wong, Jenny Man-Ching
Abstract : Background: The dosing intensity of antithymocyte globulin as induction therapy in heart transplantation remains controversial. We sought to evaluate the efficacy and safety of rabbit antithymocyte globulin at a total dose of 4.5 mg/kg compared with <4.5 mg/kg. Methods: This was a retrospective study of consecutive patients who underwent heart transplantation from January 2016 to December 2018 at a single quaternary care center. Exposure was defined as full antithymocyte globulin (4.5 mg/kg total) induction compared with partial (<4.5 mg/kg) induction. The primary outcome was the incidence of The International Society for Heart and Lung Transplantation 1990 acute cellular rejection grade 2 or above at 2 y. Secondary outcomes were all-cause mortality, number of infections, and time to therapeutic tacrolimus levels. Cox proportional hazard models were used to compare rejection rates and mortality. Results: Of 201 patients, 61 received partial and 140 received full induction. There was no difference in the cumulative incidence of cellular rejection grade 2 or above (18% versus 11.4%, P = 0.209) within 2 y. The adjusted hazard ratio was 1.45 (confidence interval: 0.62-3.37, P = 0.388) for partial compared with full induction for any grade rejection. Landmark survival analysis conditional on survival to 1 mo showed no difference in mortality ( P = 0.239). There was no difference in the incidence of infection within 3 mo of transplant (partial 29.5% versus full 20.0%, P = 0.140). Both groups achieved therapeutic tacrolimus levels by day 7 after initiation. Conclusions: There was no difference in overall risk for any grade cellular rejection between partial or full dose induction therapy. Additionally, there was no difference in medium-term mortality from landmark survival analysis. Abstract :